A Labor Market Theory of Earnings Distribution - Parker, Simon Charles (Journal of Income Distribution®, 1997)
A simple theory of the labor market is presented in which the short end of the market sells. A flexible parameterisation of the theory yields an earnings distribution density function which is closely approximated by the well-known beta and gamma specifications. Apart from providing a theoretical rationale for these tractable and closefitting specifications, the theory suggests that the parameters of the beta distribution (this distribution encompassing the gamma as a special case) can be interpreted in terms of the structure of labor markets. This has implications for why earnings distributions take their commonly observed positive skew, as well as for wider issues including the relationship between employment and equality.